Exploring the Pedagogical Process of Contrabass Learning through Édouard Nanny’s Études: A Qualitative Case Study of Technical and Musical Skill Development in Higher Education - Putri, Windi Yuliansari; Sukanta; Gunara, Sandi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to describe the pedagogical process of contrabass instruction in the Music Education program through the use of Édouard Nanny’s études and to analyze the development of students’ technical and musical skills following the instructional process. The research employed a qualitative approach using a case study method. The participants were students from the Music Education program at Universitas Pendidikan Indonesia (UPI), selected through purposive sampling. Data were collected through participant observation, in-depth interviews with students and lecturers, and document analysis, including sheet music and learning notes. The data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing and verification. The findings indicate that Édouard Nanny’s études effectively enhance students’ fundamental contrabass techniques, particularly in bowing, fingering, and shifting. In addition, these études contribute to the development of students’ musical abilities, including dynamics, articulation, and phrasing. Students reported feeling both challenged and motivated to practice consistently due to the progressive structure of the études. Overall, the results suggest that Édouard Nanny’s method can serve as an effective pedagogical approach for contrabass instruction in higher education. The études not only support the mastery of fundamental techniques but also promote the development of more advanced musical skills. Future research may explore how Édouard Nanny’s études can be pedagogically adapted within Indonesian higher music education, particularly in response to existing instructional and curricular challenges.